Life Threatening Complication during Treatment of Erysipelas due to Undiagnosed Ischemia of the Calf - Tomasz Brzeziński; Tomasz Ostrowski; Maciej Skórski (Case Reports in Medicine)
Erysipelas is a superficial skin infection due to streptococci strains, which usually responds well to conservative treatment. Coexisting undiagnosed ischemia of the extremity may lead to severe complications. 57-year-old man developed large, circumflex ulceration of his right calf within two weeks before the admission after three-month treatment of erysipelas. Computer angiography showed chronic occlusion of the superficial femoral artery and the above knee popliteal artery. Rapid debridement of the wound took control over the infection. Patient required complex vascular procedure which allowed to prepare the ulcer for meshed skin grafts. Patient was discharged home on 64th hospital day with completely healed ulcer.